Body Mass Index and Memory Across 18 Years in the Wisconsin Longitudinal Study. Issue 1 (11th February 2022) - Moorman, Sara M; Kobielski, Sara
Abstract: Background: Body weight is a modifiable risk factor for dementia, but results have been mixed as to the ages at which normal body weight is markedly preferable to overweight or obesity. This study assessed the association between change in body mass index (BMI) over 2 periods of the life course with change in memory between the ages of 65 and 72 for males and females. Methods: Participants were 3 637 White high school graduates, born in 1939, from the Wisconsin Longitudinal Study. The statistical analyses were fixed-effects regression models, with moderation terms to test for sex differences. One set of models examined change in BMI between ages 54 and 65, and the other set examined change in BMI between ages 65 and 72. In both cases, cognitive change occurred between ages 65 and 72. Results: Greater increases in BMI were associated with a greater decline in immediate recall for females only, both contemporaneously and following a lag. Increases in BMI were associated with greater contemporaneous—but not lagged—declines in both delayed recall and digit ordering for both males and females. Conclusions: The present study adds to the evidence that for White, high school educated Americans, weight gain in midlife and young-old age is a risk factor for memory decline. Results vary according to the timing of the weight gain, the aspect of memory measured, and participant sex.